Evaluating Curcumin Intake on Metabolism-Related Genes in Drosophila melanogaster - Jonathan Elbert Karsten Halim; Asbah Asbah; Nadila Pratiwi Latada; Mukarram Mudjahid; Usmar Usmar; Risfah Yulianti; Firzan Nainu (International Journal of Biomedical Science and Travel Medicine, 2024)
Background Aging entails a gradual deterioration of physiological functions within the body. Current research provides evidence suggesting that curcumin may extend the lifespan of fruit flies by mitigating the effects of aging. However, the precise concentration of curcumin necessary to induce favorable phenotypic and molecular outcomes in fruit flies has yet to be determined. Method The study utilized the capillary feeder (CAFE) assay on male Oregon-R flies, and examined the expression of the srl and pepck genes through the reverse transcriptase quantitative PCR (RT-qPCR) method. Case An elevation of curcumin consumption was examined in the treatment groups that were provided with feed containing curcumin concentrations of 50 Î¼M and 250 Î¼M. This observation is consistent with the increased lifespan noted in the Drosophila groups consuming higher concentrations of curcumin. Meanwhile, molecular analysis at the expression level of the srl and pepck genes revealed no significant change in gene expression between the treatment and control groups. Conclusion The use of the CAFE assay assists researchers in quantitatively measuring the amount of curcumin intake in Drosophila melanogaster. However, the consumption of curcumin in this experiment did not demonstrate a significant impact on the metabolism-related genes of Drosophila, srl and pepck genes.